Management Challenges in an Infant With Pentalogy of Cantrell, Giant Anterior Encephalocele, and Craniofacial Anomalies: A Case Report. Issue 9 (1st November 2018) - Hubbard, Richard; Hayes, Seth; Gillis, Holly; Lindsey, Spencer; Malhotra, Prashant; Wani, Tariq; Tobias, Joseph D.; Beltran, Ralph
Abstract : Pentalogy of Cantrell is a rare syndrome consisting of midline abnormalities involving the heart, sternum, abdominal wall, and the anterior and pericardial diaphragm. This combination of defects places patients at particular perioperative risk and requires individualized management during anesthetic care. The following report documents the management of a patient with pentalogy of Cantrell, whose condition was further complicated by severe midline craniofacial abnormalities, including large anterior encephalocele, deficient mandible, tethered tongue, and cleft palate. The case offers insight into the complexity of care in this unique patient population.